Establishing a human bone marrow single cell reference atlas to study ageing and diseases - Lee, Nicole Yee Shin; Li, Mengwei; Ang, Kok Siong; Chen, Jinmiao (Frontiers in Immunology, 2023)
Ageing in the human bone marrow is associated with immune function decline that result in the elderly being vulnerable to illnesses. A comprehensive healthy bone marrow consensus atlas can serve as a reference to study the immunological changes associated with ageing, and to identify and study abnormal cell states. We constructed a human bone marrow atlas using publicly available single cell transcriptomic data of 145 healthy samples encompassing a wide spectrum of ages ranging from 2 to 84 years old. We first characterised the changes in cell population sizes with respect to age and the corresponding changes in gene expression and pathways. Overall, we found significant age-associated changes in the lymphoid lineage cells. The naïve CD8 T cell population showed significant shrinkage with ageing while the effector/memory CD4 T cells increased in proportion. We also found an age-corelated decline in the common lymphoid progenitor population, in line with the commonly observed myeloid skew in haematopoiesis in the elderly. We then employed our cell type-specific ageing gene signatures to develop a machine learning model that predicts the biological age of healthy individuals and those with blood diseases. Finally, we demonstrated how to identify abnormal cell states by mapping disease samples onto the atlas. We accurately identified abnormal plasma cells and erythroblasts in multiple myeloma samples, and abnormal cells in acute myeloid leukaemia samples.